(untitled) (Bangladesh Journal of Zoology, 2025)
Indian major carps are key species in the Halda River, both as symbols of the region and as crucial contributors to the aquatic ecosystems and fisheries industry in Bangladesh. While previous research has examined various aspects of this river, there has been a lack of studies focusing on accurately quantifying the number of eggs collected and fry produced, as well as comparing fry production at different sites (such as mud scoops and cemented cistern). This information is essential for understanding population dynamics, assessing reproductive success, and evaluating the habitat quality of fish communities. In our study, we recorded a total of 13,502 kg of eggs collected from 314 boats. The estimated total fry production was 413.163 kg, with 98.82 kg of fry hatched from 93 rectangular mud scoops, 192.377 kg from 141 cemented rectangular cisterns, and 108.59 kg from 20 circular cistern. An independent t-test comparing fry production rates at the different hatching sites showed that the average fry production rate was highest in rectangular cisterns (3.74 ± 0.13), followed by circular cisterns (3.03 ± 0.10), and lowest in mud scoops (2.26 ± 0.059). It was also noted that the heightened turbidity caused by hilly torrents plays a significant role in facilitating the natural spawning of Indian Major Carps in the river. Bangladesh J. Zool. 52(3): 197-207, 2024